Game Lino dalam Pembelajaran Bahasa Inggris Materi Many Things Kelas VII Sekolah Menengah Pertama - Nora Maita Sari; Lidya Indah Putri (Journal of Pedagogy and Online Learning, 2022)
English is an international language where many countries use English in their daily life, such as in Malaysia. English with "Many Things" material, which is a material in English learning that teaches students to get to know the objects around them, not only knowing them but here students also learn how to write them. The problem in real life is that books do not play a role in children learning English because the books only display text and pictures so that many students do not know how to pronounce the English they are learning. With this Lino game, students can get to know the objects around them by writing the names of the objects displayed in the game and listening to how to kiss what they have written. This game serves to make it easier for children to learn English quickly, and not only that, with this game, students in learning also feel entertained by the attractive animation display.